Analisis Penerapan Lean Warehousing terhadap Pengurangan Lead Time pada Industri Manufaktur Indonesia - Arandra Swari Khairunnisa; Usep Surahman; Hanissa Okitasari (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
The manufacturing industry in Indonesia continues to face warehouse operational inefficiencies that contribute to prolonged lead times and disrupted material flows. This study aims to identify research characteristics and lean warehousing implementation practices, analyze dominant types of waste, and evaluate their impact on lead time reduction. A systematic literature review (SLR) was conducted on seven eligible articles, complemented by bibliometric analysis using VOSviewer based on keyword co-occurrence. The findings indicate that value stream mapping (VSM), process activity mapping (PAM), and fishbone diagram are the most frequently applied tools. Waiting, transportation, and overprocessing were identified as the dominant wastes across all reviewed studies. Bibliometric analysis reveals that the keywords lead time and warehouses exhibit the highest connectivity and density, indicating their central role in the research landscape. Consistent implementation of lean warehousing proved to be significantly and positively effective in improving time efficiency, with an average lead time reduction percentage of 15.8%, ranging from 4.5% to 32.5%. These findings demonstrate that lean warehousing is an effective approach to improving warehouse operational efficiency in the manufacturing sector